Antidepressant monotherapy compared with combinations of antidepressants in the treatment of resistant depressive patients: A randomized, open-label study. (February 2013) - Bares, Martin; Novak, Tomas; Kopecek, Miloslav; Stopkova, Pavla; Cermak, Jan; Kozeny, Jiri; Höschl, Cyril
Abstract Objective. This randomized, 6-week, open-label study compared efficacy of CAD and antidepressant monotherapies (ADM) that had been chosen according to clinical judgment of the attending psychiatrist. Methods. A total of 60 inpatients (intent-to-treat analysis) with depressive disorder (≥ 1 unsuccessful antidepressant treatment) were randomly assigned to the interventions. The responders who completed the acute phase of study, were evaluated for relapse within 2 months of follow-up treatment. The primary outcome measure was change in the Montgomery–Åsberg Depression Rating Scale (MADRS) and response was defined as a ≥ 50% reduction of MADRS score. Results. Mean changes in total MADRS score from baseline to week 6 for patients in both treatment modalities were not different (ADM = 13.2 ± 8.6 points; CAD = 14.5 ± 9.5 points; P = 0.58). The analysis of covariance performed for significantly higher value of imipramine equivalent dose in CAD group showed only a non-significant between-group difference for total MADRS change (P = 0.17). There were also no differences between groups in response rate (ADM = 48%; CAD = 58%) and number of drop-outs in acute treatment as well as proportion of responders' relapses in the follow-up. Conclusion. Both treatment modalities produced clinically relevant reduction of depressive symptomatology in acute treatment of patients with resistant depression and their effect was comparable.